Membangun Desa di Desa Lame, Kec. Leuwimunding, Kabupaten Majalengka, Jawa Barat. Pada program Medeka Belajar Kampus Merdeka (MBKM) - Eka Juliar; Agi; Muhammad Adlan Rosyadi; Khaeril Anwar Nawawi; Ari Ayu Arimba; Assa Fazri Maulida; Nabila Asiyah Purwati; Indra Permana (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Building a Village in Lame Village, Leuwimunding District, Majalengka Regency, West Java. In the Medeka Belajar Kampus Merdeka (MBKM) Village Building program, we realize one of the Tri Dharma of higher education, namely the field of service. The purpose of implementing this program is that students are expected to gain learning experience through involvement in the community who directly find, formulate, solve and overcome problems in the field. The target audience of the village development that we do is designing and designing and making a Budget Plan (RAB) for the infrastructure of the Sports Center (GOR), Shop House (Ruko), Foodcourt, in Lame village, Majalengka Regency. The MBKM Building Village model is utilized as an intracurricular activity that combines the implementation of the Tridharma of Higher Education with the method of providing knowledge and work experience to us in planning, implementing and supervising village development activities, by applying the knowledge of the courses taught as supporting the implementation of MBKM Building Village activities, so that the final report of the activity is submitted as an assessment of the courses taught.